Microwave hyperthermia-responsible flexible liposomal gel as a novel transdermal delivery of methotrexate for enhanced rheumatoid arthritis therapy. (17th November 2021) - Shen, Qiying; Tang, Ting; Hu, Quan; Ying, Xiaoying; Shu, Gaofeng; Teng, Chong; Du, Yongzhong
Abstract : Schematic of MTX-loaded temperature-sensitive flexible liposomal gel combined with microwave for treatment of RA. Abstract : Methotrexate (MTX) as an anti-inflammatory drug for the treatment of rheumatoid arthritis (RA) through oral and injectable administration is still problematic in the clinic. Herein, a MTX-loaded thermal-responsible flexible liposome (MTFL) incorporated within a carbomer-based gel was prepared as a novel transdermal agent (MTFL/Gel) for effective treatment of RA. It was found that MTFL had an average size of approximately 90 nm, which could rapidly release the drug under thermal conditions. The prepared MTFL/Gel could remarkably increase the MTX skin permeation as compared with free MTX, which was possibly due to the deformable membrane of flexible liposomes. Moreover, the results suggested MTFL/Gel could lead to a remarkably enhanced RA treatment when in combination with microwave hyperthermia. The superior ability of MTFL/Gel to alleviate RA response was attributed to the excellent skin permeation, thermal-responsible drug release, and synergistic anti-arthritic effect of MTX chemotherapy and microwave-induced hyperthermia therapy. Overall, the MTFL/Gel with dual deformable and thermal-responsible performances could be used as a novel promising transdermal agent for enhanced treatment of RA.